Exploring Music Video Experiences and Their Influence on Music Perception. (August 2022) - Dasovich-Wilson, Johanna N.; Thompson, Marc; Saarikallio, Suvi
Streaming music videos on the internet is an increasingly popular music listening activity that has remained virtually unexplored within music psychology. Studies of the role of music in film, as well as empirical research investigating the influence of audio-visual media and memory, have shown that visual information can have a profound effect on how music is perceived and remembered. The current study aimed to create a framework for understanding music video (MV) experiences by finding out when and why individuals choose to engage with this form of media, how these experiences contribute to the perception of musical meaning and influence affective outcomes, and whether these effects carry over to subsequent listening experiences. An online questionnaire study was designed, and data were collected from 34 participants with a mean age of 22.4 years (SD = 2.79). Abductive analysis of the qualitative data was conducted based on theories derived from topical areas of music psychology research. A framework was devised which illustrates MV listening experiences over four temporal stages: Intention, Attention, Reaction, and Retention (IARR). The IARR framework provides novel insights into MV listening experiences and outcomes by shedding light on how extra-musical information can have a long-term influence on the perception of music's meaning and affective quality.